PSXIII-24 Effect of wet versus dry feeding on digestibility, growing performance, carcass composition, and meat eating quality of finishing pigs - Vazquez, Nestor Arce (J Anim Sci, 2019)
The aim of this study was to evaluate the effect of feeding finishing pigs either dry (DF) feed (sorghum-soybean meal based diet; 16% CP, 3200 kcal ME/kg) or wet (WF; 1water:1DF) on digestibility, growing performance, carcass composition, and meat eating quality. Sixteen (Yorkshire-Landrace x Duroc) crossbred pigs (68.4 ± 2.4 kg initial BW) were individually housed and randomly assigned (4 barrows and 4 gilts) to the dietary treatments (n = 8) for five weeks. Feed was offered daily in two portions at 0800 and 1500 h. BW and feed intake were measured weekly to calculate ADG, ADFI, and G:F. Digestibility was measured on week 5 after quantitatively collecting fresh feces during 24 h. After slaughtering, carcass measurements were recorded, and chemical composition and eating quality was analyzed in samples of loin taken at 10(th) to 12(th) rib. Results were statistically analyzed with SPSS for a completely randomized design with 2 treatments and mean comparisons were performed using Tukey. Digestibility of DM, OM, and energy was greater (P < 0.05) for DF than WF. Final BW (108.4 vs 101.9 kg) and ADG (1.043 vs. 0. 990 kg/d, respectively) was higher (P < 0.05) for WF than DF. DF-fed pigs ate less at week 5 and had less G:F at week 3 than WF-fed pigs (P < 0.05). Hot and cold carcasses and ham were heavier (P < 0.05) in WF-fed pigs. Loin, rib, and shoulder weights were similar between treatments. Dietary treatment had no effect (P > 0.05) on the protein, ash, and carbon content, water retention, and pH of meat. Values of hardness, and chewiness in the meat were lower (P < 0.05) for pigs fed WF. In conclusion, finishing pigs fed WF had better growth performance, and heavier carcasses, but similar meat characteristics relative to pigs fed DF.